Wooden breast myopathy links with poorer gait in broiler chickens. (17th December 2018) - Norring, M.; Valros, A.; Valaja, J.; Sihvo, H-K.; Immonen, K.; Puolanne, E.
Abstract : Wooden breast myopathy, a condition where broiler breast muscles show a hardened consistency post-mortem, has been described recently. However, it is not known how wooden breast myopathy affects the bird activity or welfare. Altogether, over 340 birds of five commonly used commercial hybrids were housed in 25 pens, and sample birds killed at ages of 22, 32, 36, 39 and 43 days. Their breast muscle condition was assessed post-mortem by palpation. The birds were gait scored and their latency to lie was measured before killing. For further behavior observations, one affected and healthy bird in 12 pens were followed on 5 days for 20 minutes using video recordings. The connection of myopathy to gait score and activity was analyzed with mixed models. A higher gait score of wooden-breast-affected birds than that of unaffected birds (2.9 ± 0.1 v . 2.6 ± 0.1, P < 0.05) indicated a higher level of locomotor difficulties over all age groups. The wooden-breast-affected birds had fewer crawling or movement bouts while lying down compared with unaffected ( P < 0.05). Wooden breast myopathy-affected birds were heavier (2774 ± 91 v . 2620 ± 91 g; P < 0.05) and had higher breast muscle yield (21 ± 1 v . 19 ± 1%; P < 0.05) than unaffected birds overall. Older birds had longer lying bouts, longer total lying time, fewer walking bouts, more difficulties to walk and to stand compared with younger birds ( P < 0.05). Birds with poorer gait had longer total lying time and fewer walking bouts ( P < 0.05). Birds with greatest breast muscle yield had the largest number of lying bouts ( P < 0.05). It was concluded that wooden breast myopathy was associated with an impairment of gait scores, and may thus be partly linked to the common walking abnormalities in broilers.